Women unsilenced: our refusal to let torturer-traffickers win - Sarson, Jeanne (FriesenPress, 2021)
"Women Unsilenced explores the impact of unthinkable violence committed against women and girls through multiple perspectives-women's recall of life-threatening ordeals of torture, human trafficking, and organized crime, society's failure to recognize and address such crimes, and close examinations of how justice, health, political, and social systems perpetuate revictimizing trauma. Written by retired public health nurses who include their own experiences helped give voice and understanding to women who have been silenced. This book discloses their "underground" caring work and offers "kitchen table" research and insights, using women's storytelling on multiple platforms to educate readers on the unimaginable layers of perpetrators' modus operandi of violence, manipulation, and deceit. At times raw, painful, and shocking, this book is an important resource for those who have survived such crimes; professionals who support those victimized by torturers and traffickers; police, legal professionals, criminologists, human rights activists, and educators alike. It reveals how healing and claiming one's relationship with/to/for Self is possible." --Amazon.com